2012
DOI: 10.1136/bmjopen-2011-000314
|View full text |Cite
|
Sign up to set email alerts
|

Laterality, hand control and scholastic performance: a British birth cohort study

Abstract: ObjectivesTo use simple measures of laterality and hand control that can identify a greater risk of poorer scholastic ability, potentially signalling suboptimal hemispheric lateralisation.DesignAnalysis of material from a birth cohort study.SettingMembers of the National Child Development Study, a British birth cohort study following people born in 1958.Participants10 612 children who undertook tests at age 11 years.Primary outcome measuresTeacher-administered tests of non-verbal general ability, verbal genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…A more recent study [82] using a multiple regression approach, showed that the Mayringer and Wimmer's [81] reanalysis suffered from statistical problems and that the lower scores close to the point of equal hand skill reported by Crow et al [25] are part of a general monotonic relationship of laterality to cognitive ability, which is independent of overall hand skill. Additionally, our findings are in accordance with recent studies [83,84] which indicated that mixed handedness compared to right handedness was associated with poorer scholastic performance. Overall from the aforementioned studies [25,[82][83][84] we could conclude that mixed handedness could aid in the recognition of children who are at risk for academic problems.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A more recent study [82] using a multiple regression approach, showed that the Mayringer and Wimmer's [81] reanalysis suffered from statistical problems and that the lower scores close to the point of equal hand skill reported by Crow et al [25] are part of a general monotonic relationship of laterality to cognitive ability, which is independent of overall hand skill. Additionally, our findings are in accordance with recent studies [83,84] which indicated that mixed handedness compared to right handedness was associated with poorer scholastic performance. Overall from the aforementioned studies [25,[82][83][84] we could conclude that mixed handedness could aid in the recognition of children who are at risk for academic problems.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, our findings are in accordance with recent studies [83,84] which indicated that mixed handedness compared to right handedness was associated with poorer scholastic performance. Overall from the aforementioned studies [25,[82][83][84] we could conclude that mixed handedness could aid in the recognition of children who are at risk for academic problems.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies have found that variability in lateralized brain structures, functions, or behaviors is weakly associated with cognitive or behavioral performance, including verbal ability and scholastic achievement . For example, Bjork et al . analyzed data on 10,612 children from a British birth cohort and observed an association between mixed‐handedness and slightly reduced performance on school tests, including tests of verbal ability and mathematics.…”
Section: Variations Of Asymmetrymentioning
confidence: 99%
“…On the other hand, left‐handed individuals are often talented, more likely to have higher IQs, may have greater intermanual coordination, smaller asymmetries in hand skills, and less lateralization in language dominance than right‐handers . Recently, mixed‐handedness (not left‐handedness) was related to poorer mental abilities …”
Section: Introductionmentioning
confidence: 99%